Interactions of polymyxin B with lipopolysaccharide-containing membranes. (22nd September 2021) - Goode, Alice; Yeh, Vivien; Bonev, Boyan B.
Abstract : Polymyxin B uses bacterial LPS as docking receptor to cross the outer membrane. Abstract : Bacterial resistance to antibiotics constantly remodels the battlefront between infections and antibiotic therapy. Polymyxin B, a cationic peptide with an anti-Gram-negative spectrum of activity is re-entering use as a last resort measure and as an adjuvant. We use fluorescence dequenching to investigate the role of the rough chemotype bacterial lipopolysaccharide from E. coli BL21 as a molecular facilitator of membrane disruption by LPS. The minimal polymyxin B/lipid ratio required for leakage onset increased from 5.9 × 10 −4 to 1.9 × 10 −7 in the presence of rLPS. We confirm polymyxin B activity against E. coli BL21 by the agar diffusion method and determined a MIC of 291 μg ml −1 . Changes in lipid membrane stability and dynamics in response to polymyxin and the role of LPS are investigated by 31 P NMR and high resolution 31 P MAS NMR relaxation is used to monitor selective molecular interactions between polymyxin B and rLPS within bilayer lipid membranes. We observe a strong facilitating effect from rLPS on the membrane lytic properties of polymyxin B and a specific, pyrophosphate-mediated process of molecular recognition of LPS by polymyxin B.